PENGARUH SOCIAL MEDIA MARKETING PADA APLIKASI HALODOC MELALUI PERCEIVED VALUE - Latif Ar Rafi; Robert Kristaung (STMIK Widuri Jakarta, 2024)
The purpose of this research is to see, test and analyze the influence of Social Media Marketing on Percieved Value, Purchase Intention, Willingness to Pay Premium Price, and Electronic Word of Mouth as well as the positive influence of Percieved Value on Purchase Intention, Willingness to Pay Premium Price, and Electronic Word of Mouth and the positive influence of Social Media Marketing on Purchase Intention, Willingness to Pay Premium Price, and Electronic Word of Mouth mediated by Perceived Value. Data was obtained from the results of a questionnaire distributed to 200 respondents who had purchased Halodoc services twice in the last 3 months via social media. Data testing was carried out using Structural Equation Model (SEM) analysis. The results of this research show that Social Media Marketing has a positive influence on Purchase Intention. Social Media Marketing has a positive influence on Willingness to Pay Premium Price. Social Media Marketing has a positive influence on Electronic Word of Mouth. Social Media Marketing has a positive influence on Perceived Value. Perceived Value has a positive influence on Purchase Intention. Perceived Value has a positive influence on Willingness to Pay Premium Price. Perceived Value has a positive influence on Electronic Word of Mouth. Perceived Value mediates the positive influence of Social Media Marketing on Purchase Intention. Perceived Value mediates the positive influence of Social Media Marketing on Willingness to Pay Premium Price. Perceived Value mediates the positive influence of Social Media Marketing on Electronic Word of Mouth.